Gasification and tar removal characteristics of rice husk in a bubbling fluidized bed reactor. (1st October 2016) - Kook, Jin Woo; Choi, Hee Mang; Kim, Bo Hwa; Ra, Ho Won; Yoon, Sang Jun; Mun, Tae Young; Kim, Jae Ho; Kim, Yong Ku; Lee, Jae Goo; Seo, Myung Won
Abstract: Technology for converting biomass such as rice husk into a useable energy sources are key to address energy consumption issues. The effects of temperature (600–900 °C), equivalence ratio (ER, 0.15–0.3), and addition of catalyst on the gasification characteristics of rice husk were investigated in a bubbling fluidized bed reactor with an inside diameter of 0.067 m and a height of 1.55 m. As the reaction temperature and ER were increased, the concentrations of CO and CO2 in the product gas decreased. Slight increases in CH4 and H2 concentrations were also observed with increasing temperature. Throughout the temperature range of interest, an increase in ER resulted in decrement of both the higher heating value of the product gas and the cold gas efficiency. Furthermore, the effect of operating condition and addition of bed material were determined in a bubbling fluidized bed reactor. An increase in reaction temperature and ER decreased the tar content. The addition of calcined dolomite and olivine in the bed material reduced the amount of tar during rice husk gasification in a bubbling fluidized bed reactor. These results have the potential to be applied to the conversion of biomass into a useable energy source.